2019
DOI: 10.1186/s12917-018-1722-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection of low-dose gentamicin for the treatment of recurrent or persistent uveitis in horses: Preliminary results.

Abstract: BackgroundDespite appropriate medical therapy, many horses with equine recurrent uveitis continue to suffer from recurrent bouts of inflammation. Surgical intervention via the pars plana vitrectomy or suprachoroidal cyclosporine implant placement may control and/or prevent recurrences, however, these procedures may be contraindicated, unavailable, or declined by an owner. Thus, an effective adjunctive treatment option may help to improve the clinical outcomes in those situations. There are several anecdotal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 29 publications
(42 reference statements)
1
60
0
13
Order By: Relevance
“…It can be speculated whether achieved doxycycline concentrations in the current case induced an ocular anti-inflammatory effect. Similar considerations hold true for the low-dose intravitreal gentamicin (4 mg) injection, which successfully controlled different stages of inflammation in horses with recurrent or persistent uveitis 38. In a second case series,39 potential antibiotic properties addressing leptospiral-induced ERU have been suggested.…”
Section: Discussionmentioning
confidence: 88%
“…It can be speculated whether achieved doxycycline concentrations in the current case induced an ocular anti-inflammatory effect. Similar considerations hold true for the low-dose intravitreal gentamicin (4 mg) injection, which successfully controlled different stages of inflammation in horses with recurrent or persistent uveitis 38. In a second case series,39 potential antibiotic properties addressing leptospiral-induced ERU have been suggested.…”
Section: Discussionmentioning
confidence: 88%
“…The currently most promising alternative treatment option of equine recurrent uveitis is the intravitreal injection of low-dose gentamicin. A recent study shows that up to 88,1 % of 59 horses that received 4 mg of intravitreal gentamicin did not show recurrent or persistent ocular inflammation with a minimum of 30 days between treatment and follow-up (Fischer et al 2019). And another study showed that 91,8 % (56 of 61) treated eyes did not show ocular inflammation over a period that ranged between two and 96 months after treatment (Kleinpeter et al 2019).…”
Section: Alternative Methods Of Treatmentmentioning
confidence: 99%
“…Dwyer et al described that Appaloosas have an 8.3 times higher chance of developing uveitis than other equine breeds (Dwyer et al 1995). A recent study showed that Appaloosas with equine recurrent uveitis had a significant risk of developing recurrences after intravitreal treatment with low-dose gentamicin (Fischer et al 2019) and another study showed that leopard colored horses had a significantly higher risk to have a REC after vitrectomy (Schinagl 2017). One study evaluated the genetic risk factors for Appaloosas, such as a marker in the TRPM1 gene in the ECA1 region responsible for their spotted coat color and two different markers in the region for the equine major histocompatibility complex (Fritz et al 2014).…”
Section: Breed Coat Color and Agementioning
confidence: 99%
See 1 more Smart Citation
“…In this prospective study Britta Fischer and colleagues in the USA described an intravitreal gentamicin injection technique and the associated complications, and reported the effects of the injection on the clinical signs of uveitis .…”
Section: Intravitreal Gentamicin Injection For Uveitismentioning
confidence: 99%